Whole cowpea meal fortified with NaFeEDTA Reduces iron deficiency among ghanaian school children in a malaria endemic area - Abizari, A.-R.; Moretti, D.; Zimmermann, M.B.; Armar-Klemesu, M.; Brouwer, I.D. (Journal of Nutrition, 2012)
Cowpeas, like other legumes, contain high amounts of native iron but are rich in phytic acid (PA) and polyphenols (PP) that inhibit iron absorption. NaFeEDTA may overcome the combined inhibitory effect of PA and PP. Our objective was to test the efficacy of NaFeEDTA-fortified cowpea meal in improving iron status of school children in a malaria endemic area. We conducted a double-blind, controlled trial with 5- to 12-y-old school children from 2 rural communities in northern Ghana (n = 241). Eligible children were randomly assigned to 2 treatment groups to receive either cowpea meal fortified with 10 mg Fe/meal as NaFeEDTA, or an identical but nonfortified cowpea meal. Meals were provided 3 d/wk for a period of ;7 mo under strict supervision. Mass deworming and malaria antigenemia screening and treatment were carried out at baseline and 3.5 mo into the trial. Consumption of cowpea flour fortified with NaFeEDTA resulted in improvement of hemoglobin (P < 0.05), serum ferritin (P < 0.001), and body iron stores (P < 0.001) and reduction of transferrin receptor (P < 0.001) compared with nonfortified flour. Fortification resulted in a 30 and 47% reduction in the prevalence of iron deficiency (ID) and iron deficiency anemia (IDA) (P < 0.05), respectively. The results indicate that fortification of cowpea flour with NaFeEDTA overcomes the combined inhibitory effect of PA and PP and, when used for targeted school-based fortification of cowpea flour, is effective in reducing the prevalence of ID and IDA among school children in malaria endemic rural northern Ghana. © 2012 American Society for Nutrition.
Keywords: Whole cowpea meal; NaFeEDTA; iron deficiency; Ghana; school children; malaria endemic area